PENGELOLAAN EMOSI ANAK DENGAN GANGGUAN ADHD DALAM MENUMBUHKAN KARAKTER DISIPLIN - Kamila Maimun, Adhofa; Azmi Wiantina, Nur; Muttaqin, Muhammad Fauzan (IKIP Siliwangi, 2025)
Children with Attention Deficit Hyperactivity Disorder (ADHD) have challenges in controlling emotions and behavior, which impacts their ability to obey rules and develop disciplined character. This study aims to analyze emotional management strategies in children with ADHD and how this management contributes to fostering disciplined character in the school environment. The method used is a study casus qualitative approach with observation, interview, and documentation techniques for teachers, parents, and students with ADHD. The results of the study indicate that an individual approach, consistency in implementing rules, emotional regulation training, and cooperation between teachers and parents play a major role in shaping children's discipline. Effective emotional management not only reduces impulsive behavior but also helps students understand the consequences of their actions. In conclusion, proper emotional management is an important foundation in developing disciplined character in children with ADHD, and requires ongoing support from various parties.